Optimum Conditions and LC-ESI-MS Analysis of Phenolic Rich Extract from Eucalyptus marginata L. under Maceration and Ultrasound-Assisted Extraction Methods Using Response Surface Methodology - Soumaya Hasni; Ghayth Rigane; Hanene Ghazghazi; Hajer Riguene; Amir Bouallegue; Olfa Khedher; Moufida A. Oueslati; Ridha Ben Salem (Journal of Food Quality)
Eucalyptus marginata L. has a significant value in traditional medicine and recently has been shown to possess many pharmacological properties in vitro. The main goal of the present study was to optimize the extraction parameters of phenolic compounds from Eucalyptus marginata L. leaves using the extraction technique assisted by ultrasound in comparison with maceration using response surface methodology as a predicted tool. Therefore, total phenolic and flavonoid contents have been optimized, taking into account four variables: extraction time, temperature, liquid-to-solid ratio, and ethanol concentration. The optimum ultrasound-assisted extraction method for total phenolic and total flavonoid contents was obtained by ensuring the following parameters: t = 49.9 min, T = 74.9°C, liquid-to-solid ratio = 39.5 ml/g, and ethanol = 58.48%. The optimum extract has been subjected to LC-ESI-MS analysis. This technique allowed us to identify ten phenolic compounds: four phenolic acids mainly gallic acid (27.77 ± 0.06 µg/g DW) and protocatechuic acid (37.66 ± 0.04 µg/g DW) and six flavonoid compounds such as quercetrin (150.78 ± 0.02 µg/g DW) and hyperoside (39.19 ± 0.03 µg/g DW). These green and efficient procedures should be a promising option to guide industrial design for the production of phenolic-rich plant extracts.